Biomimetic Nanoparticles Camouflaged in Cancer Cell Membranes and Their Applications in Cancer Theranostics - Jin, Jiefu; Bhujwalla, Zaver M. (Frontiers in Oncology, 2020)
Nanoparticles (NPs) camouflaged in cell membranes represent novel biomimetic platforms that can mimic some of the membrane functions of the cells from which these membranes are derived, in biological systems. Studies using cell membrane coated NPs cover a large repertoire of membranes derived from cells such as red blood cells, immune cells, macrophages, and cancer cells. Cancer cell membrane coated nanoparticles (CCMCNPs) typically consist of a NP core with a cancer cell plasma membrane coat that can carry tumor-specific receptors and antigens for cancer targeting. The NP core can serve as a vehicle to carry imaging and therapeutic moieties. As a result, these CCMCNPs are being investigated for multiple purposes including cancer theranostics. Here we have discussed the key steps and major issues in the synthesis and characterization of CCMCNPs. We have highlighted the homologous binding mechanisms of CCMCNPs that are being investigated for cancer targeting, and have presented our data that identify BT474 CCMCNPs as binding to multiple cancer cell lines. Current preclinical applications of CCMCNPs for cancer theranostics and their advantages and limitations are discussed.